2009
DOI: 10.1080/01421590802464445
|View full text |Cite
|
Sign up to set email alerts
|

‘They’ve all got to learn’. Medical students’ learning from patients in ambulatory (outpatient and general practice) consultations

Abstract: In the most effective teaching consultations, doctors promoted a level of participation that realized patients' and students' mutual sense of responsibility by orientating them to one another, creating conditions for them to interact, promoting and regulating discourse, helping students to perform practical tasks and debriefing them afterwards. Those broad conclusions translate into 18 practical recommendations for supervising a medical student in an outpatient clinic or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 46 publications
4
55
0
4
Order By: Relevance
“…Because the general practice clerkship is scheduled near the end of the curriculum, the participants may have been more aware of the process of professional identity formation, which may have coloured their learning experiences. Nevertheless, the basic principles of our model also resonate in findings among third year medical students regarding early patient contacts (Ashley et al 2008). We are less sure about the impact of country-related differences with respect to the culture and context of both hospital and general practice based learning settings.…”
Section: Discussionsupporting
confidence: 52%
“…Because the general practice clerkship is scheduled near the end of the curriculum, the participants may have been more aware of the process of professional identity formation, which may have coloured their learning experiences. Nevertheless, the basic principles of our model also resonate in findings among third year medical students regarding early patient contacts (Ashley et al 2008). We are less sure about the impact of country-related differences with respect to the culture and context of both hospital and general practice based learning settings.…”
Section: Discussionsupporting
confidence: 52%
“… 1–3 What students gain from such interactions might, however, come at a cost to patients. Most patients in hospital wards and out‐patient clinics are willing to be seen by students, which suggests that any harm is slight 4–11 . A study by Benson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Personalized feedback was associated with better performance and greater course satisfaction, but with no greater sense of connectedness to the instructor. Dyrbye, Cumyn, Day, and Heflin (2009) reported that students expressed concerns with communication and clarity in instruction in online learning. Moreover, Glore (2011) found that students prefer online classes that are well organized, easy to use, and contain visual elements and graphics to help them keep their attention.…”
mentioning
confidence: 97%